Language Features of the Epic "BULBUL VA GUL"(Nightingale and Flower) - Surayya Shodiyeva Salahiddin kizi (International Journal on Integrated Education, 2022)
In this article the linguistic features of the epic "Bulbul va Gul" (Nightingale and Flower) written by Salahiddin Salahi, who lived in the 18th century, are discussed, in particular, the image tools used in the work, monologue, dialogue, proverb, antonym, synonym, repetition, and the language of the author and character. This shows the poet's ability to use the lexical layers of the language. In addition, with the help of this article, we can get information about the state of the literary language of the 18th century.